Write the nth term as `C_n (x-2)^n`

Using the ratio test, the series converges is

`lim_(n-> oo) |(C_(n+1)(x-2)^(n+1))/(C_n(x-2)^n)| < 1`

Where the radius of convergence is `lim_(n-> oo) |C_n/C_(n+1)|`

Now

`lim_(n-> oo) | (C_(n+1)(x-2)^(n+1))/(C_n(x-2)^n)| = lim_(n-> oo) |((-1)^(n+1)((x-2)^(n+1))n2^n)/((-1)^n((x-2)^n)(n+1)2^(n+1))|`

` `

` ` `= lim_(n-> oo) | ((-1)(x-2)n)/(2(n+1))| = | (-(x-2))/2...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Write the nth term as `C_n (x-2)^n`

Using the ratio test, the series converges is

`lim_(n-> oo) |(C_(n+1)(x-2)^(n+1))/(C_n(x-2)^n)| < 1`

Where the radius of convergence is `lim_(n-> oo) |C_n/C_(n+1)|`

Now

`lim_(n-> oo) | (C_(n+1)(x-2)^(n+1))/(C_n(x-2)^n)| = lim_(n-> oo) |((-1)^(n+1)((x-2)^(n+1))n2^n)/((-1)^n((x-2)^n)(n+1)2^(n+1))|`

` `

` ` `= lim_(n-> oo) | ((-1)(x-2)n)/(2(n+1))| = | (-(x-2))/2 | = |(x-2)/2|`

This is less than 1 if

`| (x-2)/2| < 1`

ie if `|x-2| < 2`

`therefore` the radius of convergence is 2